2014
DOI: 10.1080/10426914.2014.892619
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification and Nanocomposite Layering of Fastener-Hole through Friction-Stir Processing

Abstract: This investigation studied the surface modification and nanocomposite layering of the cylindrical surface of a fastener-hole using friction-stir processing. A tapered tool rotates and transverses a predrilled hole that gradually expands and simultaneously stirs the surface. The stirring modifies the hole's cylindrical surface to help improve the hardness and resist against fatigue loading. Introduction of nanoparticles between the tool and the hole during the friction stirring results in formation of a nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…3,26 The remarkable microstructural changes were noticed in the processed zone due to thermal exposure of material, mixing, and intense plastic deformation. [27][28][29] FSP can locally modify the properties such as refine microstructure, increase the ductility and strength, and reduces casting defects. [30][31][32] The present work deals with the ductilization of the cast alloy via multi-pass FSP route.…”
Section: Introductionmentioning
confidence: 99%
“…3,26 The remarkable microstructural changes were noticed in the processed zone due to thermal exposure of material, mixing, and intense plastic deformation. [27][28][29] FSP can locally modify the properties such as refine microstructure, increase the ductility and strength, and reduces casting defects. [30][31][32] The present work deals with the ductilization of the cast alloy via multi-pass FSP route.…”
Section: Introductionmentioning
confidence: 99%
“…In SiC reinforced aluminum surface composite, it was reported that hardness and flexural strength of surface composite improved considerably because of the incorporation of silicon carbide particles [74]. The hardness of the Al7075/B 4 C surface composite was reported that 62% higher that of matrix [75]. It was found that hardness of Al7075/Al 2 O 3 surface composite approximately double whereas impact toughness increases up to 29% [16].…”
Section: Reinforcements and Composite Propertiesmentioning
confidence: 99%
“…The shape of frictionstir process tool play very important role, it consistsof tool shoulder and probe. Vijay and Murugan [40]have been reportedthe impact of different probe shapes (cylindrical, square, and hexagonal) in taper and untapered profile on the tensile strength of FSW Al/TiB2/10. The joint efficiency made by un-tapered square probe obsreved max tensile strength of the base materials comparison to other pin profile.…”
Section: B Effect Of Tool Profilementioning
confidence: 99%